Izboljševanje podjetniške izkušnje s pomočjo podpornega okolja v Ljubljanski urbani regiji - Marič, Miha; Marinčič, Dejan (2025)
Enhancing the Entrepreneurial Experience Through a Supportive Environment in the Ljubljana Urban Region. The monograph “Enhancing the Entrepreneurial Experience Through a Supportive Environment in the Ljubljana Urban Region” combines five chapters that analytically address key dimensions of the local entrepreneurial ecosystem: strategic approaches of the RDA LUR, human resources and mentoring-educational programs, legal mechanisms, technological support for SMEs, perceptions of the agency's digital transformation. Based on empirical data and in-depth interviews, concrete proposals are formulated for upgrading existing support systems, thereby strengthening innovation, adaptability and sustainable development of the entrepreneurial environment in the region.
Keywords: supportive environment; entrepreneurial ecosystem; mentoring and training; digital transformation; legal framework